Análise da modificação da composição corporal durante o primeiro ano do pós-operátorio de cirurgia bariátrica - Paris, Fernanda Guidi Colossi de (2012)
INTRODUCTION: It is known the potential effect of bariatric surgery on weight reduction and improvement of associated comorbidities but is still not determined the ratio obtained between the components of body weight. This study aims to verify the change in body composition during the first year of post-bariatric surgery. METHODS: Was conducted a prospective observational cohort study. Were selected 50 patients with morbid obesity who underwent bariatric surgery and who kept up the care team according to the protocol during the first year after surgery. Patients were assessed preoperatively and postoperatively for periods of one, three, six and 12 months by tetrapolar bioelectrical impedance analysis and laboratory testing of lipids and serum albumin. Data were statistically analyzed. RESULTS: The variables of body composition obtained statistical significance (p <0.001), the mean and standard deviation in the pre and one year postoperatively, are respectively: BMI: 45,8±7,5 to 30,0±4,8 kg/m²; body fat: 64,7±15,5 to 30,6±9,8 kg, body fat percentage: 51,6±4,17 to 37,3±7,6%, total cholesterol: 197,1±49,8 to 169,8±31,0 mg/dl. The reduction in BMI achieved patients withdrew from the classification of morbid obesity to obesity grade I. The decrease in body fat percentage shows a better proportion between the body components. The percentage of fat decreased significantly more in males (p=0,012). The lean body mass (p=0,000) had the highest reduction in patients operated by the SUS (Unified Health System - Government of Brazil). CONCLUSION: The change in body composition of patients in the course of the first year of post-operative RYGBP assessed by tetrapolar BIA was statistically significant for all variables, demonstrating the effectiveness of the surgical procedure and the clinical protocol set, which tends to favor a better prognosis for the health and weight maintenance of patients in the long term.